Relative Roles of CD90 and c‐Kit to the Regenerative Efficacy of Cardiosphere‐Derived Cells in Humans and in a Mouse Model of Myocardial Infarction. Issue 5 (9th October 2014) - Cheng, Ke; Ibrahim, Ahmed; Hensley, M. Taylor; Shen, Deliang; Sun, Baiming; Middleton, Ryan; Liu, Weixin; Smith, Rachel R.; Marbán, Eduardo
Abstract : Background: The regenerative potential of cardiosphere‐derived cells (CDCs) for ischemic heart disease has been demonstrated in mice, rats, pigs, and a recently completed clinical trial (CADUCEUS). CDCs are CD105 + stromal cells of intrinsic cardiac origin, but the antigenic characteristics of the active fraction remain to be defined. CDCs contain a small minority of c‐kit + cells, which have been argued to be cardiac progenitors, and a variable fraction of CD90 + cells whose bioactivity is unclear. Methods: We performed a retrospective analysis of data from the CADUCEUS trial and a prospective mouse study to elucidate the roles of c‐kit + and CD90 + cells in human CDCs. Here, we show, surprisingly, that c‐kit expression has no relationship to CDCs' therapeutic efficacy in humans, and depletion of c‐kit + cells does not undermine the structural and functional benefits of CDCs in a mouse model of myocardial infarction (MI). In contrast, CD90 expression negatively correlates with the therapeutic benefit of CDCs in humans (ie, higher CD90 expression associated with lower efficacy). Depletion of CD90 + cells augments the functional potency of CDCs in murine MI. CD90 − CDCs secrete lower levels of inflammatory cytokines and can differentiate into cardiomyocytes in vitro and in vivo. Conclusion: The majority population of CDCs (CD105 + /CD90 − /c‐kit − ) constitutes the active fraction, both in terms of therapeutic efficacy and in the ability to undergo cardiomyogenic differentiation. The c‐kit + fraction is neither necessary for, nor contributory to, the regenerative efficacy of CDCs.